CAUSES OF SPEECH DISORDERS IN CHILDREN PRESCHOOL AGE AND MAIN DIRECTIONS CORRECTIONAL TRAINING - R.V. Lashko (Academy of Cognitive and Natural Sciences, 2004)
Scientific research showed, what very often oral of schoolchildren suffer on criticin periods of her development, wich create proposition condition in order to frustration of oral on 1-2 years, on 3 years, on 6-7 years. Large meaning in correction learning nave diagnostic of different oral's abnormality.